2021
DOI: 10.1039/d1ta07413j
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism insights into the role of the support mineralization layer toward ultrathin polyamide nanofilms for ultrafast molecular separation

Abstract: In this study, a highly perm-selective thin-film composite (TFC) nanofilm was successfully developed via silicification interlayer-mediated interfacial polymerization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 60 publications
0
17
0
Order By: Relevance
“…In terms of stripe structure, the width of the stripes generally ranges from 50 to 400 nm, and the specific length (length/area) ranges from 500 to 5000 nm per μm 2 . Like the nodular structure, the stripe structures also have low heights, , which is also evidenced by the low R a (5–50 nm). Some ring structures are possibly formed by the collapse of canopy structures or large nodular structures. , Therefore, its diameter can reach several μm, while its density is much lower than a typical nodular structure.…”
Section: Classification Of Crumpled Morphologies Their Formation Mech...mentioning
confidence: 87%
See 1 more Smart Citation
“…In terms of stripe structure, the width of the stripes generally ranges from 50 to 400 nm, and the specific length (length/area) ranges from 500 to 5000 nm per μm 2 . Like the nodular structure, the stripe structures also have low heights, , which is also evidenced by the low R a (5–50 nm). Some ring structures are possibly formed by the collapse of canopy structures or large nodular structures. , Therefore, its diameter can reach several μm, while its density is much lower than a typical nodular structure.…”
Section: Classification Of Crumpled Morphologies Their Formation Mech...mentioning
confidence: 87%
“…Previous studies have deposited nanoparticles, , nanofibers, etc., on substrate surfaces. Common methods for nanomaterial deposition include vacuum filtration, ,,, spraying, , in situ growth, , etc. An ideal deposition is a single layer of nanomaterials with a suitable distance between the individual particles/fibers.…”
Section: Classification Of Crumpled Morphologies Their Formation Mech...mentioning
confidence: 99%
“…[65,121,129,232] On the other hand, alternative materials, including monolayer graphene, [174] GO, [213] continuous MOFs and COFs, inorganics, and other materials have been widely studied for NF. [8,32,33,35,40,51,65,121,129,144,228,232,[255][256][257][258][259] Among them, NATMs on carbon nanotube support showed a more competitive performance than others. The permeance and rejection were 97.6 L m −2 h −1 bar −1 and Na 2 SO 4 rejection of 93.4%, respectively.…”
Section: Nanofiltrationmentioning
confidence: 99%
“…TiO 2 also slowed the polymerization of amine monomers in the organic phase with the TMC interface and promoted the formation of ultrathin PA layers (13 nm). 137 MOF porous nanomaterials have attracted extensive research interest in recent years. 138,139 The current methods used to prepare MOF interlayers are coating, 140 ltration 141 and layer-bylayer self-assembly.…”
Section: In Situ Growthmentioning
confidence: 99%
“…The experimental and simulation results showed that when the IP reaction was performed on the surface of the substrate with a high loading of the nanomaterial interlayers, the rate for diffusion of the amine monomers from the aqueous phase to the organic phase decreased; accordingly, a thinner and more cross-linked PA layer was formed. 137 5.2 X-ray spectroscopy X-ray photoelectron spectroscopy (XPS) uses electromagnetic radiation to quantify elemental compositions. XPS characterization plays an important role in studying TFNi membranes by analyzing the elemental composition to determine whether the nanomaterial was successfully intercalated.…”
Section: Spectroscopic Techniquesmentioning
confidence: 99%